PARALLEL ALGORITHM SEARCHING OF THE OBJECTIVE FUNCTION MAXIMUM BY DYNAMIC PROGRAMMING METHOD USING CUDA TECHNOLOGY - E. N. Seredin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Parallel algorithm searching the maximum of the objective function using CUDA technology based on the modified method of dynamic programming is presented. Describes the features of parallel software implementations of the algorithm, which allows to reduce by several orders of magnitude the number of required calculations and memory usage. The results of performance software implementations of the algorithm are shown for modern processors and video cards.